1980
DOI: 10.1017/s004317450005548x
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Diclofop-Methyl and 2,4-D in Cultivated Oats (Avena sativa)

Abstract: The chlorophyll levels and growth of oat (Avena sativaL. ‘Elgin’) seedlings were drastically reduced after foliar application of diclofop-methyl {methyl 2-[4-(2,4-dichlorophenoxy)phenoxy] propanoate}. The leaves were chlorotic and necrotic with the newly emerging leaves being most affected. Plants treated with 2,4-D [(2,4-dichlorophenoxy)acetic acid] were similar to the controls. When 2,4-D was applied to intact plants in combination with diclofop-methyl the toxicity symptoms produced by diclofop-methyl were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
28
0

Year Published

1981
1981
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 5 publications
0
28
0
Order By: Relevance
“…2,4-D has also been reported to antagonize other herbicides, such as ACCase-inhibiting herbicides in wild oats, 5,18,32,33) Lolium rigidum, 19,20) and other weed species. 34) Therefore, tank-mixing 2,4-D with other herbicides should be exercised with caution.…”
Section: Discussionmentioning
confidence: 99%
“…2,4-D has also been reported to antagonize other herbicides, such as ACCase-inhibiting herbicides in wild oats, 5,18,32,33) Lolium rigidum, 19,20) and other weed species. 34) Therefore, tank-mixing 2,4-D with other herbicides should be exercised with caution.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that phytotoxicity of AOPPs to sensitive plants can be antagonized by auxin compounds, and that the explanation for this effect of antagonism should be also included in the action mechanisms of AOPPs (Barnwell & Cobb 1994; Fletcher & Drexler 1980; Kafiz et al 1989). The present study further provides evidence for antagonism of auxin compounds to AOPPs through the mixture experiment of fluazifop‐butyl with 2,4‐D (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Although the chemistry of these two groups differs substantially, they show similar selectivity between gramineous and dicotyledonous plants. For the sensitive gramineous plants, both groups induced chlorosis and necrosis in the basal part of shoots of the seedlings (Hoerauf & Shimabukuro 1979; Fletcher & Drexler 1980; Hosaka et al 1984; Haga et al 1987; Nakahira 1998). Recent studies have provided evidence that the primary action site of both herbicide groups lies in the enzyme acetyl‐CoA carboxylase (ACCase), a plastid‐localized enzyme that catalyzes the ATP‐dependent carboxylation of acetyl‐CoA to form malonyl‐CoA (Burton et al 1989; Rendina & Felts 1988; Secor & Cseke 1988; Di Tomaso et al 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Damaged plant cell membranes release cell electrolytes when leaves are immersed in water, and a technique that measures this release, percentage leakage, has been widely used to estimate plant damage such as that caused by herbicides (Fletcher and Drexler, 1980), and freezing (Flanagan and Sprague, 1961;Murray et al, 1989). It was used here as an indicator of leaf damage from slurries and this was related to visible scorch levels on the leaves.…”
Section: Introductionmentioning
confidence: 99%